2022
DOI: 10.1177/03611981221104455
|View full text |Cite
|
Sign up to set email alerts
|

How People Perceive the Safety of Self-Driving Buses: A Quantitative Analysis Model of Perceived Safety

Abstract: With the continuous development of automatic driving technology and advancements in related experimental research, the probability of traffic accidents caused by human factors has been greatly reduced. However, people are still cautious about the safety of automated driving technology. The purpose of this study was to investigate users’ perceived safety indicators and the psychological factors of their perceived safety judgment of self-driving buses. In this study, a structural model of the factors that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Kenesei et al [24] conducted a study based on the public's trust/risk/intention to use AVs and found that trust positively affects the public's intention to use (IU) AVs and also has a significant negative effect on perceived risk. Li et al's [9] study on self-driving buses is also consistent with this. Therefore, this paper makes the following hypotheses:…”
Section: Trustsupporting
confidence: 66%
See 1 more Smart Citation
“…Kenesei et al [24] conducted a study based on the public's trust/risk/intention to use AVs and found that trust positively affects the public's intention to use (IU) AVs and also has a significant negative effect on perceived risk. Li et al's [9] study on self-driving buses is also consistent with this. Therefore, this paper makes the following hypotheses:…”
Section: Trustsupporting
confidence: 66%
“…Marvin [1] conducted statistics on these studies and found that there were 119 psychological factors involved. For example, Li et al [9] found that users' acceptance and choice of autonomous buses are based on the public's perceived usefulness and perceived ease of use of the product. Yuen et al [5] found that attitude, subjective norms, and perceived behavioral control all promote the public's willingness to use SAVs.…”
Section: Research On the Intention To Use Savsmentioning
confidence: 99%
“…Additionally, scholars have also demonstrated the effects of perceived safety on trust in AVs before and during driving (Li et al, 2022;Tan et al, 2021;Zhang et al, 2019).…”
Section: Trust Model: Trust-related Subjective Perceptionsmentioning
confidence: 99%
“…These two types of perceptions are emphasized as key factors in studying changes in trust (Muir & Moray, 1996; Muir, 1994; Perkins et al, 2010). Additionally, scholars have also demonstrated the effects of perceived safety on trust in AVs before and during driving (Li et al, 2022; Tan et al, 2021; Zhang et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…They do not need to be operated by a passenger and can stop and drive on one or more defined routes by themselves. Self-driving buses have many advantages, such as reducing energy consumption, optimizing road-resource allocation, improving traffic accessibility, and increasing traffic operation efficiency [11][12][13][14][15]. Several companies around the world are already developing self-driving buses and conducting regional road tests, and some projects are ready for mass production.…”
Section: Introductionmentioning
confidence: 99%